Competition and Humiliation: How Masculine Norms Shape Men's Sexual and Violent Behaviors. (June 2019) - Fleming, Paul J.; Barrington, Clare; Maman, Suzanne; Lerebours, Leonel; Donastorg, Yeycy; Brito, Maximo O.
We use data collected from in-depth interviews with men ( n = 30) in the Dominican Republic to explore how men's concern about being perceived as masculine influences their interactions with their social networks and how those interactions drive men's sexual behaviors and use of violence. Men's sexual and violent behaviors were shaped by the need to compete with other men for social status. This sense of competition also generated fear of humiliation for failing to provide for their families, satisfy sexual partners, or being openly disrespected. In an effort to avoid humiliation within a specific social group, men adapted their behaviors to emphasize their masculinity. Additionally, men who were humiliated recouped their masculinity by perpetrating physical or emotional violence or finding new sexual partners. These findings emphasize the need for understanding these social dynamics to better understand men's violent and sexual behaviors.